Defining and supporting a professional role for pharmacists associated with traditional and complementary medicines: a cross-country survey of pharmacists - Harnett, Joanna E.; Desselle, Shane P.; Fernandes, Marcília Baticy; Yao, Dongning; Modun, Darko; Hallit, Souheil; Dabbous, Mariam; Wahab, Mohd Shahezwan Abd; Cavaco, Afonso Miguel; Magalhães, Maria; Faller, Erwin Martinez; Flores, Jennifer M.; et al. (Frontiers in Pharmacology, 2023)
Introduction: An estimated 80% of the world’s population use traditional and complementary medicine (T&CM) products as part of their healthcare, with many accessed through pharmacy. This cross-cultural study posed a set of professional practice responsibilities and actions to pharmacists related to T&CM products with a view towards developing consensus, safeguarding, and promoting the health of the public. Methods: Data was collected from 2810 pharmacists across nine countries during 2022 via a cross-sectional online survey reported in accordance with STrengthening the Reporting of OBservational studies in Epidemiology (STROBE) guideline and the Checklist for Reporting Results of Internet E-Surveys (CHERRIES). Results: Of the 2810 participants from across nine countries, 2341 completed all sections of the survey. Of these, most agreed (69%) that T&CM product use was common in the community they served but most did not have adequate training to support consumer’s needs. Over 75% acknowledged there were known, and unknown safety risks associated with T&CM use. Of 18 professional responsibilities posed 92% agreed pharmacists should be able to inform consumers about the potential risks including T&CM side effects and drug-herb interactions. The provision of accurate scientific information on the effectiveness of T&CM products, skills to guide consumers in making informed decisions, and communication with other healthcare professionals to support appropriate and safe T&CM product use were all ranked with high levels of agreement. To facilitate being effective in these responsibilities, pharmacists agreed regulatory reforms, development of T&CM education and training and access to quality products supported by high quality evidence to support their use were needed. Conclusion: General agreement from across nine countries on eighteen professional responsibilities and several stakeholder actions serve as a foundation for discussion and development of international T&CM guidelines for pharmacists.